Collagen cross-links. A mass-spectrometric and 1H- and 13C-nuclear-magnetic-resonance study. - Hunt,E; Morris,HR (Biochem J, 1973)
1. The structure of a tetrafunctional cross-link (compound C) isolated from borohydride-reduced cow skin collagen has been determined by the combined use of mass spectrometry and (1)H and (13)C n.m.r. spectroscopy. 2. A new technique, of potentially wide applicability, is described for the mass-spectrometric determination of functional groups. 3. Detailed study of protonation shifts in the (13)C spectrum has allowed an unambiguous assignment of the exact structural relationship of the component parts of the molecule. 4. New interpretations of existing data on this molecule are given.